Parametric optimization and spark erosion behaviours of synthesized niobium composite. (2021) - Girisha, L.; Karthik, S.; Kalins, B.; Bala Koteswarao, K.; Subbiah, Ram; Marichamy, S.
Abstract: The demand of new materials in modern industries has been increased due to its substance behaviours. The substance properties were altered through addition of alloying elements or change of its composition and its processing method. The gradual change of substance properties were developed through addition of reinforcement particles. For these experimental investigations, the niobium composite was considered as the work material which was fabricated through stir casting route. The boron carbide was the reinforcement particulates which were used to improve the substance properties. The niobium composite was machined through Spark Erosion Machining process (SEM). The amount of Material Removal (MR) was calculated through the difference between initial and final mass of the niobium composite. The different input factors were chosen for found the MR such as current, pulse on time and Standoff Distance (SOD). The optimization was processed through taguchi technique. The objective of the experiment was to increase the material removal from the niobium composite. The variance analysis was used to found the influential factor on MR.